2018
DOI: 10.1111/1475-6765.12301
|View full text |Cite
|
Sign up to set email alerts
|

Why accommodate minorities asymmetrically? A theory of ideological authority insulation

Abstract: Tensions between regionalist claimants and state‐wide governments remain the primary source of violent conflicts. Existing theories cannot systematically explain why and when state‐wide governments accede to such claims. Building on the partisan approaches developed so far, a theory of ideological authority insulation is constructed in this article. It is argued that the willingness of state‐wide parties to transfer authority to specific territorial entities is predominantly informed by ideological proximity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Our third hypothesis-and a main contribution of this article-is that partisan influence is moderated by the degree of authority over education policy. The literatures on territorial politics, federalism, and decentralization have studied distributions of political power across political systems and explored their causes and some consequences (Alonso, 2012;Hooghe et al, 2016;Kleider, 2018;O'Neill, 2005;Röth & Kaiser, 2019;Toubeau & Wagner, 2015). Despite this increased attention to subnational politics, much less attention has been paid to the politics of public policy-making and how policies are jointly shaped by national and subnational actors as well as by the distribution of authority.…”
Section: How Ideology and Regional Authority Shape Education Expenditurementioning
confidence: 99%
See 2 more Smart Citations
“…Our third hypothesis-and a main contribution of this article-is that partisan influence is moderated by the degree of authority over education policy. The literatures on territorial politics, federalism, and decentralization have studied distributions of political power across political systems and explored their causes and some consequences (Alonso, 2012;Hooghe et al, 2016;Kleider, 2018;O'Neill, 2005;Röth & Kaiser, 2019;Toubeau & Wagner, 2015). Despite this increased attention to subnational politics, much less attention has been paid to the politics of public policy-making and how policies are jointly shaped by national and subnational actors as well as by the distribution of authority.…”
Section: How Ideology and Regional Authority Shape Education Expenditurementioning
confidence: 99%
“…Empirically, we find that the variation within regional units over time is higher than the variation across regions within countries, which provides confidence in our approach. Moreover, recent studies have successfully demonstrated that parties' nation-wide manifestos can be used to measure party positions for sub-national parties (Kleider et al, 2018;Röth & Kaiser, 2019).…”
Section: Measuring Regional Governments' Partisan Composition and Idementioning
confidence: 99%
See 1 more Smart Citation
“…Arguments about community, belonging, or attachment have been subsumed under varying labels such as center‐periphery dynamics, persistent cultural differences, “minority nationalism,” and “territorial identity” (Brigevich, 2018; Rokkan & Urwin, 1983, p. 135; Röth & Kaiser, 2019; Zuber, 2011). They have been shown to affect governance preferences across various territorial tiers (Brigevich, 2016; Hooghe & Marks, 2016, pp.…”
Section: The Drivers Of Differential Competence Allocationmentioning
confidence: 99%
“…The collection of data on the district magnitude (DM) at the regional level over time is difficult and time consuming. However, we perform a robustness check of the main models with the data on DM for a selected group of countries and regions, kindly provided by Röth and Kaiser (2019). The results are presented in Table 9A in the Online Appendix.…”
Section: Notesmentioning
confidence: 99%